Investigation of Joining Performance and Microstructural Mechanisms of Softwood and Hardwood Dowel Joints via Rotary Friction Welding - Jian Zhang; Yuelong Li; Hai Zhu; Feng Zhang; Yuchen Zhang; Zhenhe Li; Yanfeng Li; Yujia Liu (BioResources, 2025)
Rotary friction welding of wood typically uses dowels made from the same material as the base wood or involves specific modifications to the dowels, but these methods have practical limitations and are complex. This study focused on commonly used dowel materials (softwood: Scots pine, hardwood: birch), with moisture content adjusted to 7 to 10%, and examined the welding performance and micro-mechanisms. Through orthogonal experiments, the influence of process parameters on the welding strength of both wood types was systematically investigated. The microstructures of the welded areas were analyzed using a depth-of-field microscope and scanning electron microscope (SEM) to explore the friction mechanisms. The results indicated that both Scots pine and birch dowels can be effectively welded using rotary friction. The optimal parameters were identified as follows: Scots pine dowels—hole diameter ratio of 8/12, rotational speed of 3000 r/min, feed rate of 25 mm/s; birch dowels—hole diameter ratio of 8/12, rotational speed of 2500 r/min, feed rate of 20 mm/s. Depth-of-field microscopy revealed larger weld areas and well-preserved surface structures. SEM images showed that during welding, the materials between the dowels and base wood melted, flowed, and re-solidified into a tightly bonded structure, ensuring a durable connection.